Development of Student Worksheets Based on HOTS Model Problem Based Learning to Improve Student Learning Outcomes - Sarina, Sarina; Pasaribu, Marungkil; Nurjannah, Nurjannah; Paramita, Ielda; Sani, Nurul kami (Journal of Innovative Physics Education Research, 2025)
This study aims to develop Higher Order Thinking Skills -based Student Worksheets using the Problem Based Learning model to improve student learning outcomes. This research is a Research and Development study and uses the 4D (Define, Design, Develop, and Disseminate) development model. The developed student worksheets has been validated by media experts with a score of 89.50% and by subject matter experts, showing content feasibility of 83.45% and linguistic aspects of 91.42%. The results of the pilot test through a student response questionnaire obtained an average score of 82%, which indicates a very practical category. Meanwhile, student learning outcomes showed an average score of 57.96% with a moderate category. Thus, it can be concluded that the HOTS-based  student worksheets  using the Problem Based Learning model has been tested and is feasible for use as teaching material in physics practicums.